2020
DOI: 10.3390/antibiotics9050266
|View full text |Cite
|
Sign up to set email alerts
|

Examining Safety of Biocolourants from Fungal and Plant Sources-Examples from Cortinarius and Tapinella, Salix and Tanacetum spp. and Dyed Woollen Fabrics

Abstract: Biocolourants have been investigated as alternatives to synthetic dyes. However, natural origin per se is not a label of harmlessness and research is needed to obtain safe dyes. We studied the cytotoxicity of the extracts from fungal (Cortinarius semisanguineus, Tapinella atrotomentosa) and plant (Tanacetum vulgare, Salix phylicifolia) sources and the woollen fabrics dyed with the extracts. Cytotoxicity in vitro using hepa-1 mouse hepatoma cells for 24 h and 72 h exposure was observed as the highest tolerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…2 NOESY and HMBC key correlations observed for compounds 1 and 2 malicoria-pigmentation-type, characterized by the presence of pre-AQs [e.g., flavomannin-6,6′-dimethyl ether (6)], AQ carboxylic acids [e.g., dermolutein (4) and dermorubin (5)], as well as the monomeric AQ emodin (7) and its glucoside (3). Looking at the results of our secondary metabolite investigation and thus from a chemotaxonomic point of view, the phylogenetic classification of C. rubrophyllus can be confirmed, as its pigment profile matches the profiles of both C. semisanguineus [22][23][24] and C. malicorius [15].…”
Section: Isolation and Identification Of Isolated Secondary Metabolitesmentioning
confidence: 79%
“…2 NOESY and HMBC key correlations observed for compounds 1 and 2 malicoria-pigmentation-type, characterized by the presence of pre-AQs [e.g., flavomannin-6,6′-dimethyl ether (6)], AQ carboxylic acids [e.g., dermolutein (4) and dermorubin (5)], as well as the monomeric AQ emodin (7) and its glucoside (3). Looking at the results of our secondary metabolite investigation and thus from a chemotaxonomic point of view, the phylogenetic classification of C. rubrophyllus can be confirmed, as its pigment profile matches the profiles of both C. semisanguineus [22][23][24] and C. malicorius [15].…”
Section: Isolation and Identification Of Isolated Secondary Metabolitesmentioning
confidence: 79%
“…Klaus et al investigated different extracts of L. sulphureus fruiting body and concluded that it could be applied as a food colorant, as no cytotoxic effects were provable [5]. Even though L. sulphureus fruiting bodies are edible at a young stage, and different sources state that mycelial extracts should therefore be generally recognized as safe (GRAS), the natural origin of fungal dyes does not automatically imply food safety [32]. Further studies on the safety profile of the dyed goods appear mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing need to develop environmentally friendly techniques, and biosynthesis of indigo is one of them. 38 40 The use of bioindigo could perhaps be better for the environment; because of its biodegradability and low toxicity, bioindigo has gained popularity. When we compare microorganism-produced dyes to plant-based dyes, we see that the range of natural dyes is rather limited.…”
Section: Greener Way To Produce Denimmentioning
confidence: 99%